STRATEGI GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF DI KELAS V SEKOLAH DASAR - Patmawati; Mustika, Dea (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study is to determine and examine the tactics instructors use to establish a supportive learning environment for fifth-grade pupils.  a favourable learning environment for pupils in grade V. The sources of this research are grade V teachers and fifth grade students of SDN 13 Pekanbaru. Data were collected through observation techniques and in-depth interviews to understand teachers' practices and perspectives related to formation of a supportive learning environment. Data analysis was conducted qualitatively analysis was conducted qualitatively through interview transcription and interpretation of observation data to identify key themes related to teachers' strategies. The results of the study show that grade V teachers apply three main strategies in creating a conducive learning environment, namely physical environment strategies (flexible and ergonomic classroom arrangement, managing cleanliness, tidiness, and classroom lighting, using learning resources), non-physical environment strategies (building positive and trusting relationships, creating a democratic and inclusive classroom climate, applying positive and consistent discipline, fostering student motivation and interest in learning), and organizational strategies (establishing clear classroom rules and procedures, effective management of time and transitions, forming study groups, effective communication with related parties). These three strategies synergistically contribute to the creation of a learning environment that is safe, comfortable and supports a conducive learning process in class V. Keywords: Teacher strategies, Conducive classroom, Primary school students   Abstrak: Tujuan penelitian ini adalah menentukan serta mengevaluasi taktik yang digunakan instruktur untuk membangun lingkungan belajar yang mendukung bagi siswa kelas lima. Guru dan siswa di kelas V SDN 13 Pekanbaru menjadi narasumber penelitian. Data dikumpulkan dari teknik observasi dan wawancara mendalam untuk memahami praktik dan perspektif guru terkait pembentukan lingkungan belajar yang mendukung. Analisis data dilakukan secara kualitatif melalui transkripsi wawancara dan interpretasi data observasi untuk mengidentifikasi tema-tema kunci terkait strategi guru. Hasil penelitian menunjukkan bahwa guru kelas V menerapkan tiga strategi utama dalam menciptakan lingkungan belajar kondusif, yaitu strategi lingkungan fisik (penataan ruang kelas yang fleksibel dan ergonomis, pengelolaan kebersihan, kerapian, dan pencahayaan kelas, penggunaan sumber belajar), strategi lingkungan non-fisik (membangun hubungan positif dan saling percaya, menciptakan iklim kelas yang demokratis dan inklusif, menerapkan disiplin positif dan konsisten, menumbuhkan motivasi dan minat belajar siswa), dan strategi organisasional (penetapan aturan serta prosedur kelas yang jelas, pengelolaan waktu dan transisi yang efektif, pembentukan kelompok belajar, komunikasi yang efektif dengan pihak terkait). Ketiga strategi ini secara sinergis berkontribusi terciptanya lingkungan belajar aman, nyaman, serta mendukung proses pembelajaran yang kondusif di kelas V. Kata Kunci: Strategi guru, Kelas kondusif, Siswa sekolah dasar